(untitled) (Research, Society and Development, 2021)
The treatment of rheumatoid arthritis (RA), an inflammatory autoimmune disease of chronic nature, consists of medications, exercises, patient education on the disease, and rest. Unfortunately, many drugs used for RA have been recently recognized to induce oral manifestations due to either immunosuppression or antiproliferative effects. Thus, the present study reports a case of a patient who was receiving multiple medications (methotrexate, leflunomide, and sodium risedronate) for RA and developed an extensive lip ulcerative lesion not responsive to previous treatments. The lesion management was performed using only a combination of photobiomodulation therapy (PBMT) and antimicrobial photodynamic therapy (aPDT), totalizing three laser sessions. Within 4 days, the patient no longer complained of pain and the lesion presented an advanced healing aspect. According to the current case, the combination of PBMT and aPDT seems to be a suitable alternative for the management of oral lesions in patients taking medications for RA.